Development and validation of HPTLC method for determination of fimasartan in bulk and pharmaceutical dosage form - Shraddha Badade; Manjusha Dole; Viplav Wagh (International Journal of Pharmacy and Analytical Research, 2022)
A simple, rapid, and precise high-performance thin layer chromatographic method was developed and validated for the determination of Fimasartan in the pharmaceutical dosage form. The method employed TLC 20 cm × 10 cm aluminum-backed TLC plates coated with 200μm layers of silica gel 60F254 S as the stationary phase. Toluene: methanol: ethyl acetate: formic acid (8:1.2:0.9:0.3 v/v) are used as the solvent system. The system gave a compact spot for Fimasartan (0.6 ±0.02). The spectrodensitometric scanning-integration was performed at a wavelength of 265 nm. The regression equation data for calibration plot showed a good linear relationship with r2 = 0.9997in the concentration range 800-2800 ng for Fimasartan. The method was subjected to validate for precision, accuracy, ruggedness, robustness with their forced degradation studies. The limit of quantification and limit of detection was found to be 52.81 and 160.03 respectively. This analysis proves that the given method is selective and reproducible for the determination of Fimasartan.